Microstructural Characterisations of Perovskite Solar Cells – From Grains to Interfaces: Techniques, Features, and Challenges. Issue 23 (14th September 2017) - Rothmann, Mathias Uller; Li, Wei; Etheridge, Joanne; Cheng, Yi‐Bing
Abstract: Organic‐inorganic hybrid perovskite solar cells form a new type of thin film photovoltaic technology, which has achieved extraordinary improvements in power conversion efficiency in a relatively short time. To further improve the efficiency and stability of the perovskite solar cells, it is critical to understand and control the microstructure of both the functional materials and their interfaces. Much effort has already been made to understand the microstructure of perovskite solar cells and its influence on their performance. This has proved particularly challenging due to the fragile nature of the organic‐inorganic perovskites and the consequent potential for generating artefacts through the application of the characterization methods themselves. In this progress report, an overview of some of the more commonly used characterization methods is given, their possible impact on the materials analyses is evaluated, and the latest developments in the understanding of the microstructure of perovskite solar cells are summarized. The heterogenic nature of the individual perovskite grains and the polycrystalline film as a whole is illustrated, the features and properties of the grain boundaries and the effect they can have on solar cell performance are described, and the interface characterization between the layers in the solar cell devices is discussed. Abstract : The microstructure of perovskite solar cells has been shown to have a large impact on their properties . In this progress report, some of the most important findings relating to how different microstructures influence the performance of perovskite solar cells are summarized, and the possible impact of different characterisation techniques on the results obtained from them are discussed.